2020
DOI: 10.1002/adfm.202002606
|View full text |Cite
|
Sign up to set email alerts
|

A New Concept and Strategy for Photovoltaic and Thermoelectric Power Generation Based on Anisotropic Crystal Facet Unit

Abstract: According to the classic concept of photovoltaic devices, p-n junctions and heterojunctions are indispensable for carrier separation. Herein, for the first time, a novel concept of "anisotropic crystal facet unit" is put forward and clarified for photovoltaic and thermoelectric power generation. Specifically, an "anisotropic crystal facet unit" in monocrystalline p-Cu 2 O between the {100} and the {111} crystal faces is built, which can fulfill self-motivated carrier separation, due to their natural energy dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…On the one hand, the crystal planes and defect energy levels have been reported to affect the band structure of materials. [ 44–46 ] According to the calculations, [ 47 ] the valence band mainly comes from the selenium orbitals, whereas the conduction band has a mixed antimony and chalcogenide character. The point defects of Sb 2 Se 3 mainly include vacancies, self‐interstitials, and antisites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, the crystal planes and defect energy levels have been reported to affect the band structure of materials. [ 44–46 ] According to the calculations, [ 47 ] the valence band mainly comes from the selenium orbitals, whereas the conduction band has a mixed antimony and chalcogenide character. The point defects of Sb 2 Se 3 mainly include vacancies, self‐interstitials, and antisites.…”
Section: Resultsmentioning
confidence: 99%
“…[ 45 ] On the other hand, Li et al reported that different crystal planes of Cu 2 O have different band structures. [ 44 ] Although in the study of Sb 2 Se 3 thin films, few reports prove the influence of crystal face on the band structure. Here, we speculate that the change in the crystallographic orientation of the Sb 2 Se 3 film is likely to be one of the reasons for the positive shift of the conduction and valence band.…”
Section: Resultsmentioning
confidence: 99%
“…When the time reached 10 min, the nanocubes interlaced with each other obtaining a size of about 300 nm. Subsequently, the nanocubes started to accumulate in layers and assembled into dense single-crystal film, exhibiting a large number of triangular pyramids on the surface, exposing {100} faces as shown in the three-dimensional structure diagram (Figure h) . Therefore, we can deliberately modulate two different kinds of crystal planes respectively on opposite sides (Figure a): the surface covered with {100} crystal planes and the back side consisting of {111} crystal planes.…”
Section: Liquid-phase Synthesis Methodsmentioning
confidence: 99%
“…One of the main goals in this field is to develop high‐efficiency photocatalytic materials 8,9 . Owing to improved light absorption and charge separation, heterojunction fabrication has been an attractive research hotspot and widely studied in the field of high‐efficiency solar light conversion 6,10,11 . In particular, type II heterostructure photocatalyst systems have been extensively investigated because of their ability to separate electron and hole transfer pathways, which could improve charge carriers’ separation efficiency and extend electron lifetimes, so as to greatly improve photocatalytic activity 12‐14 .…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Owing to improved light absorption and charge separation, heterojunction fabrication has been an attractive research hotspot and widely studied in the field of high-efficiency solar light conversion. 6,10,11 In particular, type II heterostructure photocatalyst systems have been extensively investigated because of their ability to separate electron and hole transfer pathways, which could improve charge carriers' separation efficiency and extend electron lifetimes, so as to greatly improve photocatalytic activity. [12][13][14] In addition, calcination, solvothermal and in situ crystallization methods are usually used to form chemical-bond contact between two semiconductors, which is conducive to the separation of photoexcited electrons and holes, 15,16 respectively.…”
Section: Introductionmentioning
confidence: 99%